2016
DOI: 10.1063/1.4962332
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-ballistic transport in GaN nanowires

Abstract: The ballistic filtering property of nanoscale crosses was used to investigate the effect of perpendicular magnetic fields on the ballistic transport of electrons on wide band-gap GaN heterostructures. The straight scattering-less trajectory of electrons was modified by a perpendicular magnetic field which produced a strong non-linear behavior in the measured output voltage of the ballistic filters and allowed the observation of semi-classical and quantum effects, such as quenching of the Hall resistance and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Figure 3a shows the output characteristics of the 50 nmlong 85 nm-wide shallow IPGFET. A large current density (I ds /w) of 1.4 A/mm was observed, which is over 9x-larger than the best IPGFET [9] based on an InGaAs quantum well, due to the much larger carrier density and very small sidewall depletion in III-Nitrides [16,17]. Figure 3b shows the transconductance of the 50 nm-long IPGFETs, revealing larger and broader g m for wider nanowires.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 3a shows the output characteristics of the 50 nmlong 85 nm-wide shallow IPGFET. A large current density (I ds /w) of 1.4 A/mm was observed, which is over 9x-larger than the best IPGFET [9] based on an InGaAs quantum well, due to the much larger carrier density and very small sidewall depletion in III-Nitrides [16,17]. Figure 3b shows the transconductance of the 50 nm-long IPGFETs, revealing larger and broader g m for wider nanowires.…”
Section: Resultsmentioning
confidence: 95%
“…The latter include electrically pumping THz sources [7][8][9], detectors [10] and modulators [5,11]. A lot of attention is also paid to the electron transport properties of the nitrides in magnetic fields to develop novel devices working as sensors and switches controlled by a magnetic field [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main concerns regarding multichannel heterostructures based on AlGaN barriers is the lattice-mismatch-induced tensile strain, which limits the number of channels that can be grown before cracking. Furthermore, it has been shown that the tensile strain is partially relaxed at free mesa edges when devices are processed, leading to side-wall depletion of carriers [21,22]. The induced non-uniformity of the carrier density could potentially be detrimental for device performance in some applications.…”
mentioning
confidence: 99%